Budaya Literasi dalam Perspektif Tanggung Jawab Sosial - David Randy; Nawiroh Vera; Umaimah Wahid (UNIVERSITAS 17 AGUSTUS 1945 JAKARTA, 2020)
AbstractThroughout 2019, Indonesia was confronted with a number of mass actions that led to riots. In many discussions on mainstream media platform as well as academic institutions, the circulation of hoaxes and fake news on social media are often used as scapegoats. President of the Indonesian Anti-Defamation Society (Mafindo), Anita Wahid explained, in 2015, there was an average of 10 hoaxes circulated in Indonesia per month. This number increased to 27 per month in 2016, 59 per month in 2017, and 96 per month in 2018. According to Central Connecticut State University, in 2016, Indonesia was on the 60th position (out of 61 countries) regarding literacy and literate behaviour. Based on Aisah, Hasra, and Sumiati's finding, it is known that as many as 61 percent of 184 respondents (Indonesian undergraduate students) couldn't identify one of the three fake news that was presented. Meanwhile, according to Dr Quinton Temby's analysis, the protests on May 21-22 in Jakarta, which led to riots, were the result of online disinformation. This type of chaos was the first time that had ever happened among democratic countries. The dependence of the Indonesian public on the social media platform can indicate a decline in public trust for the mainstream media. Temby claimed that this happened because most of Indonesian’s mainstream media were too sympathetic to the government. On this paper, the authors examine the phenomenon of the circulation of hoax and fake news in Indonesia through a multi-modal analysis. We started the study by conducting background analysis (literature reviews) on the culture of literacy in Indonesia, continuing with frame analysis of METRO TV’s news (allegedly as one of the pro-government media), then analysing the findings in the social responsibility perspective. Results of the analysis showed an increase in the number of hoaxes and false news' circulation in Indonesia. For this reason, to combat its circulation, the government's commitment is needed to foster a literate culture. The mainstream media need to increase public trust through more educative and critical programs. Social media companies need to be more active and responsive in preventing and combating the circulation of hoaxes and fake news. At the same time, the Indonesian public needs to educate themselves by increasing their understanding and knowledge.Keywords: Framing Analysis, Fake News, Hoax, Culture of Literacy, Social Responsibility Theory.AbstraksiSepanjang tahun 2019, Indonesia dihadapkan dengan sejumlah aksi massa yang berujung kericuhan. Dalam banyak diskusi di media massa mau pun institusi akademik, peredaran hoax dan fake news di media sosial sering dijadikan sebagai kambing hitam. Presiden Masyarakat Anti Fitnah Indonesia (Mafindo), Anita Wahid menerangkan bahwa pada 2015 rata-rata 10 hoax beredar di Indonesia per bulannya. Jumlah tersebut meningkat menjadi 27 per bulan pada 2016, 59 per bulan pada 2017, dan 96 per bulan pada 2018. Hasil studi di Universitas Negeri Central Connecticut tentang budaya literasi global pada 2016, menempatkan Indonesia di peringkat 60 dari 61 negara yang diteliti. Dari penelitian Aisah, Hasra, dan Sumiati, diketahui sebanyak 61 persen dari 184 responden (mahasiswa Indonesia) tidak dapat mengidentifikasi 1 dari 3 fake news yang ditampilkan. Sementara itu, Dr. Quinton Temby berpendapat bahwa aksi massa di Jakarta yang berujung kericuhan pada 21-22 Mei lalu ialah akibat dari disinformasi online. Kericuhan semacam itu merupakan yang pertama kali terjadi di negara demokrasi. Ketergantungan sejumlah rakyat Indonesia terhadap platform media sosial merupakan indikasi penurunan keperayaan publik kepada media mainstream. Temby mengklaim bahwa hal tersebut terjadi karena sebagian besar media mainstream Indonesia terlalu bersimpati kepada pemerintah. Pada penelitian ini, penulis mengkaji fenomena peredaran hoax dan fake news di Indonesia melalui analisis multi-modal. Kami memulai dari analisis latar belakang (studi pustaka) tentang budaya literasi di Indonesia, dilanjutkan dengan analisis framing berita METROTV (yang diduga sebagai salah satu media massa pendukung pemerintah), kemudian menganalisis temuan-temuan dalam perspektif tanggung jawab sosial. Hasil analisis menunjukkan adanya peningkatan jumlah sirkulasi hoax dan fake news di Indonesia. Untuk itu, dalam upaya memerangi peredarannya diperlukan komitmen pemerintah dalam menumbuhkan budaya literasi. Media massa mainstream perlu meningkatkan kepercayaan publik melalui tayangan-tayangan yang lebih edukatif dan kritis. Perusahaan media sosial perlu berperan lebih aktif dan responsif dalam mencegah dan melawan peredaran hoax dan fake news. Di saat yang sama, masyarakat Indonesia perlu mengedukasi diri melalui peningkatkan pemahaman dan pengetahuan secara mandiri.Kata Kunci: Analisis Framing, Budaya Literasi, Fake News, Hoax, Teori Tanggung Jawab Sosial